Etude de la croissance et de l'activité écophysiologique des huîtres creuses Crassostrea gigas, Crassostrea angulata et de leurs hybrides en système contrôlé - Haure, Joel; Huvet, Arnaud; Palvadeau, Hubert; Nourry, Max; Martin, Jean-louis; Boudry, Pierre; Penisson, Christian (2001)
A comparative study of the growth of the oysters Crassostrea gigas, Crassostrea angulata and their hybrids was carried out in 1999 in system controlled with contribution of the micro alga Skeletonema costatum. The results showed significant differences of the pondéral growth of the four studied progenies. The animals C. gigas had growth rates 1.4 times greater than C. angulata oysters. The hybrid progenies were shown more powerful than Portuguese oysters but are not different from the Japanese oysters. The ecophysiologic study showed that the averages of filtration and oxygen uptake, obtained by means of a three hours recording, cannot differentiate the four studied progenies. On the other hand, the calculation of the FTA (Feeding Time Activity) allowed to identify a specific behavior ecophysiologic to each progenies. The results supposed a less long time of activity of nutrition at C. angulata (84 ± 10 %) that for C. gigas (98 ± 6 %) and the hybrids (90 to 97 ± 7 %). The results of SFG (Scope For Growth) calculated according to times of activity of nutrition and oxygen uptake put in evidence 1.4 times superior report of the growth for the Japanese oyster compared with Portuguese. Une étude comparative de la croissance des huîtres Crassostrea gigas, Crassostrea angulata et de leurs hybrides a été réalisée en 1999 en système contrôlé avec apport de la micro algue Skeletonema costatum. Les résultats ont montré des différences significatives de la croissance pondérale des quatre populations étudiées. Les animaux C gigas ont présenté des taux de croissance 1,4 fois supérieurs aux huîtres C. angulata. Les populations hybrides se sont montrées plus performantes que les huîtres portugaises mais ne se différencient pas des japonaises. L'étude écophysiologique a montré que les moyennes de filtration et de consommation d'oxygène, obtenues au moyen d'un enregistrement de trois heures, ne peuvent différencier les quatre populations étudiées. En revanche, le calcul du FTA (Feeding Time Activity) a permis d'identifier un ...